Facility maintenance and management: a health care case study - Shohet, Igal M.; Lavy, Sarel (International Journal of Strategic Property Management, 2017)
Contemporary trends in healthcare services provision tend toward the increased use of community based healthcare centers. This study on the concepts of healthcare provision hypothesizes that in the future, the main source of healthcare services will be a network of community based clinics which will be responsible for the majority of primary and ambulatory care. This concept implies that a network of community clinics equipped with state of the art telemedicine will be established with a wide geographical dispersion. The implications for healthcare facilities in terms of the resources and performance of the built environment are investigated by reference to the Israeli healthcare system. This paper reflects the results of research on healthcare facility management over the past 10 years. Comparison of the performance and maintenance of hospital facilities and community clinics reveals that the maintenance and performance of clinic facilities have the potential to combine improved healthcare facility services with cost-effective facility management and maintenance.